Saprobic status and Bioindicators of the river Sutlej - C, Sharma; Singh, Uday Bhan (Journal of Research in Biology, 2014)
Saprobic status and bioindicators of river Sutlej was conducted at (S1) Ropar Headworks, (S2) downstream after the confluence with BudhaNallah, (S3) Harike before the confluence with river Beas, (S4) Harike before the confluence with river Beas. Water samples were collected on the monthly basis for two consecutive years (November, 2009-October, 2011), on the basis of saprobic classification given by Sladecek (1973), (S1) could be categorized as oligosaprobic, (S2) as polysaprobic, (S3) as mesosaprobic, and (S4) as meso-polysaprobic. Data on the Palmer’s Algal Index values revealed that S2 and S4 were grossly polluted, S1 was least polluted, whereas in S3, there were chances of medium degree of organic pollution. Bioindicator organism may have higher frequency index and they are major peak forming organisms at different stations and in different seasons. The results also indicate that the bioindicator species may also behave as peak forming organisms and their abundant depends upon diverse parameters.